Evaluation of Internal Quality Audit Procedures for ISO 9001:2008 Submissions at Casablanca Club - David Yanto Daniel Mahulae (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to find out how the procedures and effectiveness of internal quality audits for submitting ISO 9001: 2008 certificates to companies. To be able to achieve the writing of this research, it cannot be denied that data and information are important factors. To obtain the data and information needed in this study, the authors collect data and information through research or research activities. The research method used is descriptive analysis method, which is a research method carried out by collecting, presenting, and analyzing company data based on existing facts with data collection techniques such as field studies, interviews, observations, and library research. Based on descriptive analysis of the research, the following results were obtained: a) Internal quality is a means to achieve a score determined by external parties, b) Internal quality audits have been carried out properly by auditing every existing department, c) Companies measure quality audit performance internally, namely by the actions taken by each personnel in their respective departments on any existing findings where after the action a management review is carried out.